A Translation Analysis of Noun Phrase from English into Indonesian on Unilever's Products - Al-anshory, rofi, Dr. Anam Sutopo, S. pd., M. Hum, Siti Fatimah, S. Pd., M. Hum (2015)
ABSTRACT This study aims at describing the translation analysis of noun phrase from English into Indonesian on Unilever's products. classify the translation shifts of noun phrase found on Unilever's products and describe the equivalence translation on the label of Unilever's product. The type of this reseach is descriptive qualitative reseach. In collecting the data, the writer uses documentation. The data are analyzed using translation analysis theory based on A Linguistic Theory of Translation by Catford (1965) there are steps to collect data, namely: the writer looks for the Unilever's products. Then finds out the occurence of noun phrase on the Unilever's products, the writer identify the noun phrase which are found on the Unilever's products and underlining the noun phrase, the writer writes them on computer, the writer codes the data for each classifications. The collected data are analyzed by using A Linguistic Theory of Translation by Catford. The results of the reseach show that the writer finds 75 sentences on the label of Unilever's products, the writer finds 101 noun phrases on the Label of Unilever\s product. The writer may classify translation shift into four types. They are level shift, structure shift, class shift and intra system shift. Its consist of 22 data or 21,78% belong to level shift of noun phrase, 58 data or 57,42% belong to structure shift of noun phrase, 10 data or 9,90% belong to class shift of noun phrase and 11 data or 10,89% belong to intra system shift of noun phrase. The writer finds 75 sentences, the writer can classify equivalent translation into two types. They are 110 data or 93,22% belong to equivalent translation and 8 data 6,78% belong to non equivalent translation. The result of this study is that the company still make errors in translating text on the label product. Therefore, there is necessity of repack producing. Keyword: Linguistic, Translation Analysis, and Translation shift.